Crise nas licenciaturas: o novo perfil do professor da educação básica no Brasil sob a égide do neoliberalismo - Pereira, Leoclécio Dobrovoski Silva (2018)
The present dissertation had as general objective understanding how the crisis in the degrees impact in the formation and transformation of the teachers’ profile in the basic education in Brazil since the 1990’s, under the impacts of neoliberal policies, particularly after 1995, when the State reform begins in a systematized way in that country. The research was conducted through a review of literature and documents of official agencies from the 1990s. The new public management, presented by the State as an alternative for the solution of financial, bureaucratic and efficiency problems in the administration of public affairs, aims to the excellence of work and results charged by the community and the requirement of international mechanisms such as workforce training, investment and foreign capital attraction and better levels of learning. The example of Minas Gerais is emphasized, as it was the first Brazilian state to implement the new public management with the Management Shock, whose main objective was to balance revenue and expenditure, as well as to make Minas the best state to live, according to the government. For the critique, the balance was made with financial leeway that only disguised the problems of the State and, for the education workers, there was the loss of rights and autonomy. Regarding the formation, both Law n. 9394/1996 and the 2015 National Curriculum Guidelines for teacher education emphasize the preparation of the new labor force for capital and consumption by reinventing (and readapting) the new, fluid, stratified, and flexible social subject. Moreover, the crisis in degrees is consubstantiated on several fronts, namely by the upward devaluation that is being suffered in the last decades, by policies and new public management, by social deprestige, by lack of attractiveness, by illness and abandonment of the profession.